Management Protection of the Ecosystem a Comparative Study - Roaa Razzaq Abed , Researcher (lark, 2022)
Administrative law possesses, via administrative control bodies, an array of corrective and preventative legal instruments for achieving public order in all its branches (security, health, and public tranquility). It tries to conserve environmental aspects unrelated to human and public safety. Accordingly, the close connection between administrative law and environmental protection regulations minimizes the likelihood of pollution. Individual choices, bans, licensing, and other administrative control mechanisms must be implemented. In addition, it underlines the significance of administrative penalties established in the law that gives the administration the ability to impose these sometimes material and sometimes immaterial punishments. Including highly effective modern scientific directions for saving the environment. And work on amending or replacing legislation that does not comply with the requirements of providing environmental protection to reach a protected ecosystem that functions in balance and flows after pollution has affected all elements of the environment. Including water, air, soil, and food, because of technological advancements and the dissemination of destructive rumors.
Keywords: legal protection, administrative law, environmental system, environmental pollution, administrative control, administrative control bodies.